2019
DOI: 10.3390/en12132545
|View full text |Cite
|
Sign up to set email alerts
|

Correlation Analysis between Land Use/Cover Change and Air Pollutants—A Case Study in Wuyishan City

Abstract: Land use changes have significantly altered the natural environment in which humans live. In urban areas, diminishing air quality poses a large threat to human health. In order to investigate the relationship between land use/cover change (LUCC) and air pollutants of Wuyishan City between 2014–2017, an integrated approach was used by combining remote sensing techniques with a landscape ecology methods. Annual, seasonal, and weekly mean values of air pollutant (SO2, NO2, CO, PM10, O3, PM2.5, black carbon) conce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
11
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 63 publications
3
11
0
1
Order By: Relevance
“…Although the locations index is different, this model shows that within a one-kilometer radius of bare land, there are several congestion points, so PM10 has unhealthy air quality index. This finding is also supported by previous research [30] that PM10 concentrations are usually higher in bare land than plantations. Landsat 8.…”
Section: Methodssupporting
confidence: 90%
“…Although the locations index is different, this model shows that within a one-kilometer radius of bare land, there are several congestion points, so PM10 has unhealthy air quality index. This finding is also supported by previous research [30] that PM10 concentrations are usually higher in bare land than plantations. Landsat 8.…”
Section: Methodssupporting
confidence: 90%
“…Positively significant correlation was detected between AOD and water body (Table 3 and Figure 6). This finding was consistent with the results from Luo et al (2001) [61] and Che et al (2009) [59], but contrary to those from Zhu et al (2019) [56] and Halim et al (2020) [34]. Rich water resources and the crisscross water network in our study area were partly responsible for it.…”
Section: Limitations and Research Prospectssupporting
confidence: 91%
“…The data were downloaded from USGS (data portal: https://earthexplorer.usgs.gov/) with cloud coverage less than 10%, which met the study requirements. The data preprocessing of the remote sensing images, including geometric correction, radiometric calibration, atmospheric correction, image enhancement, image mosaic, and clipping was performed in ENVI5.3 (ITT VIS, Boulder, Colorado, USA) [56].…”
Section: Lulc Classification Based On Landsat 8 231 Supervised Classification Methodsmentioning
confidence: 99%
“…On the other hand, a large number of scholars have carried out relevant research on the impact of urbanization, economic development, and population changes on LUCC, which also took Ghana's oil city, Western Kenya as example respectively (Acheampong et al, 2018;Kogo et al, 2021), especially the change of construction land of LUCC, which is also the core content of research on urban sprawl and unlimited urban expansion (Hasse and Lathrop, 2003;Kuang et al, 2016). Some scholars have also begun to study the relationship between air quality and LUCC taking Wuyishan J o u r n a l P r e -p r o o f City as a case, and found that different land use types and different air quality factors are closely related (Zhu et al, 2019).…”
Section: Literature Review and Analytical Frameworkmentioning
confidence: 99%